PENDIDIKAN KARAKTER BERDASARKAN PENGAMALAN NILAI - NILAI MORAL PANCASILA SEBAGAI JATI DIRI BANGSA INDONESIA - Luh Suryatni (UNIVERSITAS DIRGANTARA MARSEKAL SURYADARMA, 2017)
Character is a trait which a combination of internalized moral values from outside ourselves and potentials existing in us. These potentials are gifts from God as our identity then become our nature. Later, on our journey in life, we will choose which nature will became the essential value in life. For example, honesty, it cannot be taken for granted. Honesty need to be strived for in each of our actions. You can be known about having a character when you able to perform honestly. Whereas identity crisis of a nation should not be allowed to drag on. There should be an efforts to deal with it, in order for the nation to find its true identity while rekindling its spirit and soul, rooted by the nation character itself there will be no doubt when facing various challenges and problems. Therefore, the development of national character is aimed to construct personal and family sustainability which become the foundation of the national sustainability. The fragility of national sustainability can be caused by the weakness in personal and family sustainability. So far, this weakness is due to personal sustainability just focusing in the competency and knowledge rather than studying the character development also. Personal character is a key which is not touched of all fronts. The main problem is the absence of handbook in how to develop a character. Thus, effective effort is required to develop the character of a nation through education and training for everyone, at every occasion in form of implementation of the existing and ongoing education also training revitalization. Keyword : Character Education, The Moral Values Of Pancasila, and Identity Of The Nation Of Indonesia